CHEAP QURBAN CAMPAIGN: A QURBAN HADITH ANALYSIS WITH JADZA‘AH LAMB PERSPECTIVE OF FIQH AL-TAYSÎR - Muhammad Kudhori; Anindya Mitra Raisnur Putri; Mundhir Mundhir (Hukum Islam, 2023)
The ritual of sacrificing animals known as Qurban is one of the most prominent worships in Islam. Nevertheless, on account of the highly criteria of qurban’s animals, the price of animals often very excessive. Hence, qurban is considered as an expensive kind of worship for many Indonesian Muslims, to be specific, for the middle to low economic class of Muslims. Whereas in fiqh literature, there is an opinion that it is permissible to perform sacrifice with jadza‘ah sheep whose price is more affordable. Unfortunately, this opinion is not well known among the Indonesian Muslim community. This article will analyze the hadith of qurban with jadza‘ah sheep in the perspective of fiqh al-taysîr. This article is considered as qualitative research that use literature references that are relevant to the theme. The methods of research are content analysis and descriptive-analytical method. Fiqh al-taysîr emphasizes a notion that are easier for Muslims to implement. In its implementation, fiqh al-taysîr considers these matters; a more moderate aspect, emergency factor, easier opinion, being careful in deciding between obligatory and sunnah, free from mahdzab fanaticism, facilitating things that cannot or might be difficult to avoid, taking into maqâṣid syarî'ah consideration and applying the rules: changes in fatwas due to the change of times, places, conditions, and habits. In the context of the criteria for jadza‘ah sheep as an alternate animal for Qurban, the concept of fiqh al-taysîr takes the opinion of ulemas who state that jadza‘ah sheep are sheep that are perfectly six months old and the price is relatively affordable in price, thus they are easier to practice by the Muslim community of the middle to lower economic class.